Accentuating cardiovascular events in Sibutramine-treated patients - Radeyah Waseem; Raza, Mahnoor; Aleena Aftab (Journal of the Pakistan Medical Association, 2022)
Sibutramine has been used as an anti-obesity drug, sold under the brand name of Meridia, among others. However, it was banned in various countries after a statistically impactful finding that it increases the risk of cardiovascular events even in patients who were not at a predisposed risk. Despite these findings, Sibutramine is still prescribed in Pakistan, in spite of the high prevalence of cardiovascular diseases in our population. In this letter, we have summarized the long-known, and recent findings regarding Sibutramine and have also provided the statistics to empower our reasoning. We believe that this letter will prove to be a valuable asset in spreading awareness regarding Sibutramine within the medical community in Pakistan. Continuous...